Piranske notarske knjige (Zvezek 5) = The Notary Books from Piran (Vol. 5) Fragmenti (1289-1305) = Fragments (1289-1305) - Mihelič, Darja (Thesaurus memoriae, 2009)
The work is a critical edition of the preserved fragments of five notary codices from Piran (1289-1305) with notes made by the notary Dominicus Petenarius. Notaries entered into notary codices the essential features of business transactions in stenographic form, specific writing and simple Latin. This is a valuable type of sources for the study of medieval and later history. The entries portray the economic and social life of cities and their surroundings, their administration, judicial system, everyday life, population development, urban image, as well as culture and arts, all of which serve the purposes of research conducted by experts in various fields. The edition is equipped with a standard critical apparatus and an accompanying study which is also translated into English. The main part of the text encompasses the transliteration of the manuscript comprising 518 agreements with different contents. Each is marked with a successive number, defined with regard to its content and dated. The specific features of the original and inconsistencies in writing are described in notes. The work comes with an index of names, a subject index and a list of entries in which each entry is marked with the original annotation of the page in the original, date, type of contents, short summary of the contents and the page in the publication.